COVID-19: A crisis of the female self-employed - Daniel Graeber; Alexander Kritikos; Johannes Seebauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
We investigate how the economic consequences of the pandemic, and of the governmentmandated measures to contain its spread, affected the self-employed relative to employed individuals in Germany and, secondly, to what extent the female self-employed were more strongly hit than their male counterparts. For our analysis, we use representative real-time survey data in which respondents were asked about their situation during the COVID-19 pandemic. Our findings indicate that self-employed individuals were much more likely to suffer income losses than employees. Among the self-employed, women were 35% more likely to experience income losses than men, as women are disproportionately working in industries that are more severely affected by the COVID-19 pandemic. We conclude that future policy measures intended to mitigate such shocks should account for this variation in economic hardship.
Keywords: L26; J16; J31; J71; I18; 330; self-employed; COVID-19; income; gender; representative real-time surveydata; decomposition methods